Studentification in Bloemfontein, South Africa - Ackermann Anton; Visser Gustav (Bulletin of Geography. Socio-Economic Series)
Studentification is a global phenomenon that has been prominent in urban geographical discourse since the large-scale expansion of higher education in the early 1990s. In many developed and developing world countries, expansion in student enrolment has outstripped the ability of institutions of higher learning to provide adequate accommodation. Similar trends have been recorded in South Africa. The task of this paper is to investigate studentification as experienced in one of South Africa’s secondary cities. The paper draws attention to the economic, socio-cultural, and physical characteristics of this form of student housing on host locations. It is argued that studentification holds both positive and negative impacts for the host communities of Bloemfontein. Finally, it is suggested that studentification in South Africa requires greater research attention.